2006
DOI: 10.1017/s1740925x07000476
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of avoidant behaviors and pain by the anti-inflammatory tyrosine phosphatase SHP-1

Abstract: The protein tyrosine phosphatase SHP-1 is a critical regulator of cytokine signaling and inflammation. Mice homozygous for a null allele at the SHP-1 locus have a phenotype of severe inflammation and are hyper-responsive to the TLR4 ligand LPS. TLR4 stimulation in the CNS has been linked to both neuropathic pain and sickness behaviors. To determine if reduction in SHP-1 expression affects LPS-induced behaviors, responses of heterozygous SHP-1-deficient (me/+) and wild-type (+/+) mice to LPS were measured. Chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…IFN-β treatment of MS patients did not change the levels of IL-4, but significantly decreased plasma levels of IL-13. In addition, we quantified the secretion of the NF-κB-responsive pro-inflammatory cytokines TNF-α and IL-6, since it was previously shown that a deficiency in SHP-1 leads to higher expression of these cytokines [22; 40; 68; 74; 76; 77]. The plasma levels of TNF-α and IL-6 were significantly higher in MS patients compared to normal subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-β treatment of MS patients did not change the levels of IL-4, but significantly decreased plasma levels of IL-13. In addition, we quantified the secretion of the NF-κB-responsive pro-inflammatory cytokines TNF-α and IL-6, since it was previously shown that a deficiency in SHP-1 leads to higher expression of these cytokines [22; 40; 68; 74; 76; 77]. The plasma levels of TNF-α and IL-6 were significantly higher in MS patients compared to normal subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Arginase enzymatic activity was measured as previously described [68]. Briefly, PBMCs were lysed in RIPA buffer and incubated in 10 mM MnCl 2 and 0.5 M L-arginine at 37°C for 75 min.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we quantified the secretion of the NF-kBresponsive proinflammatory cytokines TNF-a and IL-6 from macrophages of MS patients compared to normal subjects, because it was previously shown that a deficiency in SHP-1 leads to higher expression of these cytokines. 9,27,62,[64][65][66] Macrophages were cultured for 18 h with either media alone, TLR ligands, or TNF-a and the supernatants were analyzed for the presence of TNF-a or IL-6 (Figure 5b and c). Constitutively, the levels of TNF-a and IL-6 were slightly but significantly elevated in supernatants of macrophages from MS patients compared to normal subjects.…”
Section: Elevated Expression Of Nf-jb Dna-binding Activity and Tnf-a/mentioning
confidence: 92%
“…31 Briefly, PBMCs were lysed in RIPA buffer and incubated in 10 mM MnCl 2 and 0.5 M L-arginine at 371C for 75 min. After the assay was stopped by addition of H 3 PO 4 , 1-phenyl-1,2-propanedione-2-oxime (Sigma, St Louis, MO, USA) was added and the samples were incubated at 1001C for 60 min.…”
Section: Transduction Of Shp-1-expresssing Lentiviral Vectormentioning
confidence: 99%